Effective Communication Between Physicians and Nurses: A Cornerstone for Patient Safety - Alsiddiqi, Zohair Ahmad; Alkazmi, Mohammad Mahmood; Almugati, Khlwd Ghzae Saad; Almuqati, Najla Ghazi S; Alnakhliy, Enas Mohammad Hassan; Alotaibi, Najah Mohammed; Alshammari, Shamah Abdullkarim Saoud; Alkhamis, Khatoon Mouyd; Alsabi, Laila Mansour; Aqeel, Amnah Abdo; et al. (Journal of Posthumanism, 2024)
Effective communication between physicians and nurses is the foundation of patient safety and high-quality care. In complex healthcare environments, every message shared, whether verbal or digital, directly influences patient outcomes. Miscommunication has been identified as one of the leading causes of medical errors, jeopardizing safety and continuity of care.